Strategic environmental assessment in areas beyond national jurisdiction: existing regimes, challenges, and prospects - Song, Yuanming; Mao, Zhengkai; Zhang, Zhijun (Frontiers in Marine Science, 2024)
As a system based on domestic law, strategic environmental assessment (SEA) can take environmental factors into consideration in the formulation of policies, plans, and programmes, and has received much attention in the field of environmental governance of areas beyond national jurisdiction (ABNJ). The recently adopted “Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas beyond National Jurisdiction” (BBNJ Agreement) incorporates SEA into its text, but the BBNJ Agreement has not yet entered into force. Of other existing schemes governing ABNJ, some lack provisions on SEA, and some do not set SEA as a binding legal obligation. Conducting SEA in ABNJ faces several challenges, including fragmented rules and reluctance on the part of countries, which lead to unsatisfactory results. Therefore, this study suggests that the BBNJ Agreement should collaborate with regional treaties and international organizations in the future to complement and reinforce current systems and regulations, improving compatibility among them. At the same time, consideration should be given to identifying the protection of BBNJ as a common concern of humankind (CCH) to strengthen the implementation of future SEAs.